WNT3A promotes the cementogenic differentiation of dental pulp stem cells through the FOXO1 signaling pathway - Dongmei Cheng; Yang Bao; Xue Wang; Haidong Xiang; Tianyuan Guo; Yong Du; Zhiyong Zhang; Han Guo (European Journal of Medical Research)
Abstract Background Dental pulp stem cells (DPSCs) possess capability of multidirectional differentiation, and their cementogenic differentiation potential enables them to participate in cementum repair and regeneration. The molecular mechanisms underlying cementogenic differentiation of DPSCs remain unclear. Methods DPSC data set GSE138179 was retrieved from gene expression omnibus (GEO) database. Weighted gene co-expression network analysis (WGCNA) was employed to identify significant modules. Pathway enrichment exploration was conducted utilizing gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), Gene Set Enrichment Analysis (GSEA), and Metascape tools. CIBERSORT was utilized to analyze immune cell infiltration analysis. The comparative toxicogenomics database (CTD) was utilized for the validation of core targets. Subsequently, cell experiments were conducted to validate the core targets. Changes in protein expression related to the FOXO1 signaling pathway, cell cycle, and apoptosis were evaluated using western blotting (WB). Results Differentially expressed genes (DEGs) associated with DPSC cementogenic differentiation were predominantly enriched in crucial pathways such as the signaling pathway, cell apoptosis, and Wnt signaling pathway. Bioinformatics analysis confirmed WNT3A as a pivotal biomarker for DPSC cementogenic differentiation, and WNT3A was highly expressed in the cementogenic differentiation group. Western blotting results demonstrated that compared to the DPSC group, molecules such as Caspase-3, Caspase-9, FAS, P53, and BAX were downregulated in the CDDPSC group, suggesting reduced apoptosis. Furthermore, upregulation of WNT3A expression in CDDPSC–OE further suppressed the expression of these apoptotic molecules, suggesting a mitigated apoptotic response. Downregulation of WNT3A expression in CDDPSC–KO resulted in increased expression of apoptosis-related molecules, thereby enhancing apoptosis. Conclusions WNT3A is highly expressed in the cementogenic differentiation of DPSC, and WNT3A mediates FOXO1 pathway to promote differentiation of dental pulp stem cells into cementogenic differentiation, thus realizing the formation and maintenance of cementum tissue.